Tugas Guru Pendidikan Khusus dalam Menangani ABK di Sekolah Inklusi - Vieto Budi Utomo; Adhy Putri Rilianti (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2023)
This  research  examines  the  duties  of  special  education  teachers  in  inclusive schools.  The  research  method  is  a literature review using  articles  related to research titles published in the 2018-2021 period. The first search identified 24 articles, and 10 were evaluated using a thematic data approach. The results of the study show the pedagogic and non-pedagogic functions of special education teachers' tasks. Non-pedagogic tasks include emotional support, consultation and facilitation between teachers, students and parents. Pedagogic tasks include teaching, giving assignment instructions, helping students focus on completing assignments,  making  PPI  (individual  learning  programs),  conducting assessments, and managing student behavior. The research results also show the relevance  of  special  education  teacher  education  and  collaborative  learning between special education teachers and general education teachers. The last section discusses the limitations of the study and further research.